Analisis Penggunaan Media Pembelajaran dalam Meningkatkan Kemampuan Berpikir Kreatif Siswa - Rohayu; Deni Adi Putra; Kunti Dian Ayu Afiani (Universitas PGRI Adi Buana Surabaya, 2021)
This research aims to analyze the use of instructional media in improving students' creative thinking skills. The methodology used in this research is the meta-analysis research method. The object of this research is 10 relevant journals whose variables are in accordance with the research topic. Based on the analysis and discussion that has been carried out through a review of 10 journals. It can be concluded that the use of media can improve students' creative thinking skills with a total percentage reaching 80.74%. There are differences in the results of increasing students' creative thinking skills in each research data. This is due to the different objects of research, approaches, principles, and concepts used to analyze problems in each different research. The use of media in the learning process can improve students' creative thinking skills. Therefore, it is hoped that the teacher can understand the importance of using media in the learning process so the teacher can find out students' creative thinking skills in learning and teachers will be more creative and varied in using media during the learning process.